2014
DOI: 10.5194/acp-14-1353-2014
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on ship NO<sub>x</sub> emissions in Europe using GEOS-Chem and OMI satellite NO<sub>2</sub> observations

Abstract: Abstract. We present a top-down ship NO x emission inventory for the Baltic Sea, the North Sea, the Bay of Biscay and the Mediterranean Sea based on satellite-observed tropospheric NO 2 columns of the Ozone Monitoring Instrument (OMI) for [2005][2006]. We improved the representation of ship emissions in the GEOS-Chem chemistry transport model, and compared simulated NO 2 columns to consistent satellite observations. Relative differences between simulated and observed NO 2 columns have been used to constrain sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 59 publications
6
120
3
Order By: Relevance
“…Even if the areas are not the same, the differences seem to be remarkable. Recent investigations by Vinken et al (2014) using satellite data suggested that the officially reported ship emissions might be overestimated by about 35 %. In 2015, EMEP revised the emissions provided through their website to 644 Gg for NO x and 162 Gg for SO 2 (EMEP/CEIP, 2015).…”
Section: Ship Emission Inventorymentioning
confidence: 99%
“…Even if the areas are not the same, the differences seem to be remarkable. Recent investigations by Vinken et al (2014) using satellite data suggested that the officially reported ship emissions might be overestimated by about 35 %. In 2015, EMEP revised the emissions provided through their website to 644 Gg for NO x and 162 Gg for SO 2 (EMEP/CEIP, 2015).…”
Section: Ship Emission Inventorymentioning
confidence: 99%
“…Optimisation of the emissions of several other compounds have also been evaluated through inverse methods constrained by satellite observations, such as isoprene, methanol or formaldehyde (Stavrakou et al, 2011(Stavrakou et al, , 2009Palmer et al, 2003;Wells et al, 2014;Barkley et al, 2013), and other studies have focused on the optimisations of the emissions from different sectors, such as ships (de Ruyter de Wildt et al, 2012;Vinken et al, 2014).…”
Section: Evaluation and Optimisation Of Emissions Using Inverse Modelmentioning
confidence: 99%
“…NO 2 observations from satellite offer a globally consistent data set, albeit at coarse resolutions of 10 s to 100 s of kilometers, enabling a wide range of applications including many not feasible from in situ observations. Several studies have used satellite observations of NO 2 to evaluate chemical transport models (Martin et al, 2002;van Noije et al, 2006;Lamsal et al, 2008;Kim et al, 2009;Herron-Thorpe et al, 2010;Huijnen et al, 2010), examine spatial and temporal patterns of NO x emissions (Beirle et al, 2003;Richter et al, 2005;Kim et al, 2006;van der A et al, 2006;Zhang et al, 2007;Boersma et al, 2008a;Lu and Streets, 2012;Wang et al, 2012;Hilboll et al, 2013;Russell et al, 2010Russell et al, , 2012Duncan et al, 2013), examine NO x sources (Jaeglé et al, 2005;van der A et al, 2008;Bucsela et al, 2010;de Wildt et al, 2012;Lin, 2012;Ghude et al, 2010Ghude et al, , 2013aMebust et al, 2011;Mebust and Cohen, 2013), provide top-down constraints on surface NO x emissions Konovalov et al, 2006;Zhao and Wang, 2009;Lin et al, 2010;Lamsal et al, 2011;Ghude et al, 2013b;Vinken et al, 2014), infer NO x lifetimes (Schaub et al, 2007;Lamsal et al, 2010;Beirle et al, 2011), and estimate surface NO 2 concentrations …”
Section: Introductionmentioning
confidence: 99%